Tea Garden Lateritic Soil as a High-Temperature Desulfurization Sorbent: Effect of Oxygen on Regeneration Process. (19th July 2018) - Ko, Tzu-Hsing; Chu, Chen-Yao
Abstract : The lateritic soils collected from a tea garden were used to explore the regeneration process using different O2 contents for high-temperature desulfurization. The desulfurization and regeneration experiments were carried out using a fixed-bed reactor at 500°C and the gaseous mixture composed of 1% H2 S, 25% CO, 15% H2, and balance N2 for the desulfurization process. Experimental results showed that the regenerability is better when the air was used as a regeneration gas and the regeneration time is shortened. Multiple regeneration experiments indicated that lateritic soils can be regenerated by passing air and can thus be reused many times and its regeneration efficiency is slightly better than that regenerated by 1% O2 . The sulfur capacity after air desulfurization/regeneration cycles was examined by elemental analysis with a value ranging from 1.40% to 1.49%, and residual sulfur was detected with a value of 0.12% after the diluted 1% O2 regeneration. No sulfur was detected for the regenerated lateritic soil after air regeneration. From NMR structural identification, the 6-coordinated octahedral structure of Al and trioctahedral coordinated Si are the major Al-containing and Si-containing compounds. Broad shoulder peaks were detected after regeneration process that may be associated with the formation of aluminosilicate and further reduces the dispersion of iron on the surface of lateritic soils.